Deletion of C1ql1 Causes Hearing Loss and Abnormal Auditory Nerve Fibers in the Mouse Cochlea - Qi, Yue; Xiong, Wei; Yu, Shukui; Du, Zhengde; Qu, Tengfei; He, Lu; Wei, Wei; Zhang, Lingjun; Liu, Ke; Li, Yi; He, David Z.; Gong, Shusheng (Frontiers in Cellular Neuroscience, 2021)
C1QL1 (Complement C1q Like 1) is known to play an important role in synaptic maturation, regulation and maintenance in the central nervous system. Previous studies have shown that C1ql1 is expressed in cochlear inner and outer hair cells (IHCs and OHCs) with preferential expression in OHCs, one of the two types of auditory sensory receptor cells that play a critical role in mechanical amplification in the cochlea. We generated C1ql1 null mice to examine the role of C1QL1 in cochlear hair cells. Auditory function tests showed that C1ql1-null mice have progressive loss of OHCs and hearing at 1 month of age. Confocal microscopy shows that the number of nerve fibers innervating both IHCs and OHCs was significantly reduced. Interestingly, the soma of spiral ganglion neurons appeared to be normal under electron microscopy and no significant IHC loss was observed. Voltage-clamp recording from wild-type and C1ql1-null IHCs showed that voltage-dependent Ca++-current and exocytosis, which reflects release of synaptic vesicles, were similar. Antibody-based immunocytochmistry and confocal microscopy showed no significant reduction of pre-synaptic proteins in IHCs. Our study suggests that C1ql1 is essential for development of hair cell innervation and OHC survival and that maturation of presynaptic machinery in IHCs does not depend on innervation.